A matter of days - Kizer, Amber (New York : Delacorte Press, 2013)
In the not-too-distant future when a global pandemic kills most of humanity, a teenaged girl and her younger brother struggle to survive.
Publisher's Weekly, May 2013
Kirkus Review, April 2013
Young Adult
Keywords: Survival -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Epidemics -- Juvenile fiction; Virus diseases -- Juvenile fiction; Survival -- Fiction; Brothers and sisters -- Fiction; Epidemics -- Fiction; Virus diseases -- Fiction; Science fiction; Survival skills -- Fiction; Siblings -- Fiction; Epidemics -- Fiction; Viruses -- Fiction; Science fiction; Science fiction